Teacher-learning process based on an immersive and interactive environment - Guimarães, Marcelo de Paiva; Dias, Diego Roberto Colombo; Corrêa, Moacyr Francischetti; Brega, Jose Remo Ferreira [UNESP]; Trevelin, Luis Carlos (My University, 2013)
This paper explores the benefits of using immersive and interactive multiprojection environments (CAVE) to visualize molecules, and how it improves users’ understanding. We have proposed and implemented a tool for teachers to manipulate molecules and another to edit molecules and assist students at home. The contribution of the present research project are these tool that allows investigating structures, properties and dynamics of a molecular system which are extremely complex and comprises millions of atoms. The experience is enriched through multimedia information associated with parts of the model; for example, videos and text can be linked to specific molecule, demonstrating some detail. This solution is based on a teaching-learning process.
Keywords: Education; Data visualization; Interactive system; Virtual reality